The Influence Of Growing Agents Of Growth On Growth and Production Of Flower Cabbage Plant (Brassica Oleraceae Var. Botrytis L.) On Different Intervals Of Applications. - M Abror; Siti Azizah (Nabatia, 2017)
The purpose of this study was to determine the effect of ZPT species with different appli- cation time intervals on the growth and production of flower cabbage plants. The study was conducted in the village of Jati Utara 3 Sidoarjo from May to July 2015. The research was arranged using factorial randomized block design (RBD) which was repeated three times. The first factor is the type of ZPT used which consists of 3 levels, namely P1 (atonic), P2 (agrogibb), and P3 (young coconut water). The second factor is the applica- tion time interval, namely O1 (once every 5 days), O2 (once every 10 days), and O3 (once every 15 days). The observed parameters were plant height, number of leaves, plant wet weight, flower volume, flower diameter, and flower weight. The results showed that the treatment of ZPT types and application time intervals significantly affected plant height but did not significantly affect the number of leaves, whereas destructive observations only affected the plant wet weight. The interaction between the treatment of ZPT with the application time occurred at 36 and 43 HST observations on plant height, as well as on the observation parameters of plant wet weight. The results showed that the use of the Atonic ZPT type (P1) and application time interval of 15 days (O3) gave the best results on the growth and production of flower cabbage plants.